Pemetaan Tempat Perkembangbiakan Potensial Anopheles sp. di Tempat Wisata Pangandaran - Wawan Ridwan; Andri Ruliansyah; Asep Jajang Kusnandar; Firda Yanuar Pradani (ASPIRATOR - Journal of Vector-borne Disease Studies, 2019)
Abstract. Most Malaria cases in West Java were concentrated in the southern coast region and one of themis Pangandaran district. There were still many potential sites for Anopheles sp. breeding place inPangandaran, so that the Regency was categorized as a receptive area. This study aimed to identify thespread of potential breeding sites for Anopheles sp. in Pangandaran Regency. The data were collected usinga spatial method in all of the areas in Pangandaran District. Data collecting was done by mapping thepositive breeding sites of Anopheles sp. which was then overlayed with a map of the tourist destination inPangandaran Regency. The larvae found were identified as An. aconitus, An. annularis, An. barbirostris, An.identifinitus, An. maculatus, An. subpictus, An. sundaicus and An. Vagus. All of the species found werepotentially became malaria vectors. There seven positive breeding sites were found which six of them locatedin tourism areas that were the Districts of Pangandaran, Cimerak, Parigi, Kalipucang, Sidamulih, andCijulang. It was concluded that Pangandaran still has the potential for malaria transmission both for localtransmission and for the potential entry of imported malaria.